PPARα: A potential therapeutic target of cholestasis - Xiaoyin Ye; Tong Zhang; Han Han (Frontiers Media S.A., 2022)
The accumulation of bile acids in the liver leads to the development of cholestasis and hepatocyte injury. Nuclear receptors control the synthesis and transport of bile acids in the liver. Among them, the farnesoid X receptor (FXR) is the most common receptor studied in treating cholestasis. The activation of this receptor can reduce the amount of bile acid synthesis and decrease the bile acid content in the liver, alleviating cholestasis. Ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) have a FXR excitatory effect, but the unresponsiveness of some patients and the side effect of pruritus seriously affect the results of UDCA or OCA treatment. The activator of peroxisome proliferator-activated receptor alpha (PPARα) has emerged as a new target for controlling the synthesis and transport of bile acids during cholestasis. Moreover, the anti-inflammatory effect of PPARα can effectively reduce cholestatic liver injury, thereby improving patients' physiological status. Here, we will focus on the function of PPARα and its involvement in the regulation of bile acid transport and metabolism. In addition, the anti-inflammatory effects of PPARα will be discussed in some detail. Finally, we will discuss the application of PPARα agonists for cholestatic liver disorders.